2008
DOI: 10.2337/dc07-2288
|View full text |Cite
|
Sign up to set email alerts
|

Custom Therapeutic Insoles Based on Both Foot Shape and Plantar Pressure Measurement Provide Enhanced Pressure Relief

Abstract: OBJECTIVE -The purpose of this study was to determine whether custom insoles tailored to contours of the barefoot pressure distribution and shape of a patient's foot can reduce plantar pressures in the metatarsal head (MTH) region to a greater extent than conventional custom insoles.RESEARCH DESIGN AND METHODS -Seventy regions of elevated barefoot pressures (mean peak 834 kPa under MTHs) were identified in 20 subjects with diabetes. Foam box impressions of their feet were sent to three different orthotic suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
151
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(162 citation statements)
references
References 23 publications
8
151
2
1
Order By: Relevance
“…They found that a custom insole that its shape is coincident with plantar curvature reduces the plantar pressure more effectively [19]. Lavery et al 2005 investigated the shear stress parameter in three-layer insole that was made by plastazote foam (PLZ), Prone and EVA by using experimental testing.…”
Section: Introductionmentioning
confidence: 99%
“…They found that a custom insole that its shape is coincident with plantar curvature reduces the plantar pressure more effectively [19]. Lavery et al 2005 investigated the shear stress parameter in three-layer insole that was made by plastazote foam (PLZ), Prone and EVA by using experimental testing.…”
Section: Introductionmentioning
confidence: 99%
“…The TCC is commonly recognized as the "gold standard" in healing ulcers. Although some RCWs were demonstrated in the gait laboratory to be as effective as the TCC in off-loading the foot [7][8][9], a clinical trial by Armstrong et al [10] found that the TCC resulted in higher healing rates and a shorter time to healing than an RCW with a similar capacity for off-loading wounds. It was hypothesized that the TCC's ability to ensure compliance was responsible for the difference in healing.…”
Section: Off-loadingmentioning
confidence: 97%
“…Prefabricated inlays and shoes are routinely prescribed to high-risk patients. Numerous studies have demonstrated these to be highly efficacious in off-loading the foot [9,13,14]. Some preliminary studies have shown prescribed footwear to be effective in preventing ulcer reoccurrence [12].…”
Section: Off-loading Compliancementioning
confidence: 98%
“…The examination included vascular, neurological, dermatological and orthopedic assessments. Therapeutic insoles based on the shape and plantar pressure management and the type of shoe the subject wore were supplied to the participants if necessary (Owings et al 2008). It was hoped that this inter vention would contribute to improved compliance to the walk program and comfort of the participants.…”
Section: Ethicsmentioning
confidence: 99%